Penanaman Karakter Kebhinekaan Global Siswa Kelas V SDN Ngebel - Sintiya Rizki Aisah; An-Nisa Apriani; Indah Perdana Sari; Galih Albarra Shidiq (Alma Ata University Press, 2026)
Strengthening students’ character is a key focus in education, especially in the era of globalization that demands the younger generation to be adaptive and responsive to cultural diversity. However, in practice, primary school learning often emphasizes cognitive aspects alone, without integrating character values such as global diversity. The low level of student understanding regarding inclusivity and tolerance highlights the urgent need to develop learning models that can effectively instill these values. This study aims to determine the effect of the STEM-based I-LVEP learning model on cultivating the character of global diversity among elementary school students. This research employed a quantitative approach with data collected through observations of students and teachers. The subjects were 40 fifth-grade students at SDN Ngebel, divided into class VA as the control group and class VB as the experimental group, selected using a purposive sampling technique. The research design used was a pretest-posttest non-equivalent control group design. Data analysis was conducted using a parametric t-test (independent sample t-test). The results showed that the STEM-based I-LVEP learning model had a significant influence on students’ global diversity character. This is evidenced by the t-value (t_count = 3.336) being greater than the critical value (t_table = 1.686) at a significance level of 0.05, thus Hâ‚ was accepted and Hâ‚€ rejected. The model offers an engaging learning experience, enhances conceptual understanding and critical thinking skills, and fosters the internalization of essential life values such as inclusiveness and tolerance. Therefore, it is recommended that future research examine the impact of the STEM-based I-LVEP model on improving students' academic performance in a more comprehensive manner.